Respuesta :

Answer:

(y + 6)(y - 4)

Step-by-step explanation:

Factor the following:

[tex] \longrightarrow [/tex] y² + 2y - 24

The factors of -24 that sum to 2 are 6 and -4.

So,

[tex] \longrightarrow [/tex] y² + (6 - 4)y -24

[tex] \longrightarrow [/tex] y² + 6y - 4y - 24

[tex] \longrightarrow [/tex] y(y + 6) - 4(y + 6)

[tex] \longrightarrow [/tex] (y + 6)(y - 4)

Answer:

( y-4) ( y+6)

Step-by-step explanation:

= y^2 + ( 6 - 4)y - 24

= y^2 + 6y - 4y - 24

= y( y + 6) - 4(y + 6)

= ( y - 4 ) ( y + 6)

ACCESS MORE